Targeting of lanthanide(III) chelates of DOTA-type glycoconjugates to the hepatic asyaloglycoprotein receptor: cell internalization and animal imaging studies - Prata, M. I. M. (2006)
The characterization of a new class of hydrophilic liver-targeted agents for gamma-scintigraphy and MRI, consisting, respectively, of [153Sm]3+ or Gd3+ complexes of DOTA monoamide or bisamide linked glycoconjugates (DOTA = 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid), is reported. In vitro studies show high uptake of radiolabeled 153SmDOTAGal2 by the human hepatocyte carcinoma cell line Hep G2 containing the asialoglycoprotein receptor (ASGP-R), which is decreased to less than 50 % by the presence of its high affinity ligand asialofetuin (ASF). In vivo biodistribution, gamma-imaging and pharmaco-kinetic studies on Wistar rats using the [153Sm]3+-radiolabeled conjugates show an high uptake in the receptor-rich organ liver of the compounds containing terminal galactosyl groups, but very little uptake for those with terminal glycosyl groups. Blocking the receptor in vivo reduced liver uptake by 90%, strongly suggesting that the liver uptake of these compounds is mediated by their binding to the asyaloglycoprotein receptor (ASGP-R). This study also demonstrated that the valency increase improves the targeting capability of the glycoconjugates, which is also affected by their topology. However despite the specific liver uptake of the radiolabeled galactose-bearing multivalent compounds, the animal MRI assessment of the corresponding Gd3+ chelates shows liver-to-kidney contrast effects which are not significantly better than those shown by GdDTPA. The maximum concentration/dose ratio attained in the kidneys by the Gd3+- based CAs is considerably lower than for GdDTPA, indicating that part of the injected CAs is T1 contrast-silent, presumably when taken up into the liver. The T1 shortening effect of the Gd3+-labeled Gal-containing compounds is probably strongly diminished upon hepatocyte internalization into an endossomic vesicle via receptor-mediated endocytosis of the ASGP-R.